Implementation of the Archives Digitization Policy at the Majalengka Regency Archives and Library Department - Ignashena; Nursahidin (Al-Makki Publisher, 2026)
The rapid advancement of information technology has driven government institutions to transition from conventional archive management to electronic-based systems; yet many regional agencies still face challenges in implementing digitalisation policies effectively. This study aims to determine the implementation of archive digitalisation policies at the Regional Archives and Library Office of Majalengka Regency. The focus of the research encompasses the implementation of archive digitalisation policies, their supporting and inhibiting factors, and the efforts made to overcome implementation obstacles. This study employs a qualitative research method with a descriptive approach. Data were collected through observation, interviews, and documentation. The results indicate that the implementation of archive digitalisation policies at the Regional Archives and Library Office of Majalengka Regency has not been carried out optimally, particularly with regard to infrastructure resources. Supporting factors include inter-institutional cooperation, support from regional leadership, and effective coordination across sectors. The main inhibiting factor is the limited number of available laptops and computers, some of which are outdated models. The steps taken to address this problem include increasing the number of available laptops and computers.